اعتبا المآلات وأثرها في الفتوى دراسة مقاصدية تطبيقية في الأقليات المسلمة - Nur Syahirah Binti Mohammad Nasir (Universiti Sains Islam Malaysia, 2024)
This research studies the principle of I’tibar al-Maalat in terms of its application towards fatwa, particularly fatwa pertaining Muslim minorities issues. This discussion is established based on inductive, deductive and descriptive analysis methods, in order to understand the concept of this principle as well as to extract its implication and role in fatwa pertaining Muslim minorities’ issues and to build its parameters in its application. This study also applies empirical case studies for several Muslim minorities’ issues. Among them are conversion of women into Islam without their husbands doing the same, a marriage between Muslim and al-kitabiyyah, attending an event where alcohols are served and purchasing a property for living through conventional banking. Through the proses of interviewing selected respondents in gaining information, this study reaches the findings that I’tibar al-Maalat has a significant impact in the fatwa of Muslim minorities as it makes the fatwa applied in an appropriate manner, and as a prevention from harm and a treatment of the real problem of the musafir. It is because I’tibar al-Maalat serves as a guidance for Mufti to determine the real maslahah and mafsadah. Since it is not simple to determine the ruling of each issue, it is not feasible for a mufti to come up with a general fatwa for issues addressed, in fact it is important that the issues be considered in specific manner based on individuals and issues involved. Thus the impacts of I’tibar al-Maalat are likely to vary for each issue in determining its ruling : permissible or prohibited, which is established based on the principle of preventing harm.